Phenomenological Study: Analysis of The Management of Regionally Owned Enterprises - Hasanudin Ali; Suwito; Hartaty Hadady (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to describe and describe the meaning of reality about the conception and unravel the legal observance of the managers of the Kie Raha Mandiri Regional Company by exploring the structure of their consciousness. The method used is a qualitative method, with the author chosen phenomenological approach, which is the stage of Husserl's transcendental phenomenological analysis. Husserl's transcendental phenomenology emphasizes subjectivity and uncovers the essence of experience through merging fact and ideal. The data sources used are primary and secondary data. In contrast, the technical data collection is Observation, Interview, and Documentation, as well as data analysis using Miles And Huberman's theory, namely, data collection, data reduction, display data, and concluding. The results showed that results of this study showed that: (1) the planning aspects were not apparent both in the short, medium, and long term, the management of the core business was ineffective, the amount of capital participation was not by the profits obtained; (2) Organizing is not based on administrative principles, both HR capabilities, specialization, task hierarchy, and authority and responsibility: (3) The actuating has not run optimally, the ability of the leadership is weak, and the ability of the SDM is limited: (4) the control function of the supervisory board is still weak until it suffers significant losses